A web-based survey on adverse childhood experience, anxiety, depression, sexual behavior affecting methamphetamine use among adolescents in Bangkok, Thailand - Min Htike (2021)
Thailand is no longer a major source of illicit drugs but it has become a transit point for drug trafficking among countries in Southeast Asia, East Asia and Oceania. Bangkok is Thailand’s major metropolis where socio-economic status is high and, thus, drug dealers are targeting affluent vocational school students. A cross-sectional web-based study on methamphetamine use among vocational school students (n= 755) was conducted by randomly sampling three schools. The study explored adverse childhood experiences (ACEs), anxiety and depression in Bangkok to predict the associated factors of methamphetamine use. The reliability of the survey instruments for assessing anxiety, depression and ACEs, was tested using Cronbach’s alpha and yielded values of 0.9, 0.9 and 0.8 respectively. Chi-square test was used to assess the level of association between the methamphetamine use and each independent variable. Multiple logistic regression was performed to determine the predictors of methamphetamine use. Among 755 adolescent students aged 16-19 years, 55.0% had at least one ACE, 44.9% had been screened as having anxiety, 44.0% seemed to have depression, and 2.4% reported methamphetamine use in the previous year. After adjusting for socio-demographic factors, sexual risk factors, psychological factors, gender (Adj OR=11.70, 95% CI=1.39-98.28), school strictness on drugs (Adj OR=7.49, 95% CI=1.91-29.44), current house (Adj OR=5.54, 95% CI=1.09-28.26), condom-less first sex (Adj OR=7.28, 95% CI=2.48-21.39), depression (Adj OR=9.61, 95% CI=2.50-36.95) and family violence (Adj OR=6.03, 95% CI=1.96-18.59) were associated with methamphetamine use among adolescents. The study indicates that psychological factors, family violence and sexual risk behaviors increase vulnerability for methamphetamine use among adolescents in Bangkok. However, further qualitative research studies are warranted.